Penerapan Pembelajaran Problem Solving Diskusi Rolling dalam Meningkatkan Hasil Belajar dan Keaktifan Siswa Kelas IV pada Pelajaran IPA - Sulaefah Sulaefah; Dede Hadiansah (Lembaga Yasin AlSys, 2025)
Low learning outcomes and limited student engagement at SDN 2 Tanjung Pura are attributed to the continued use of teacher-centered instructional approaches, highlighting the need for innovation in teaching strategies. This study aims to improve student engagement and academic achievement through the implementation of the Problem Solving learning model. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart design, which includes the stages of planning, action, observation, and reflection. Data were collected through student activity observations and learning outcome tests. The findings indicate that the gradual implementation of the Problem Solving model significantly enhanced both student participation and learning outcomes. In the pre-cycle stage, only 8 out of 20 students (40%) met the minimum mastery criteria. This number increased to 12 students (60%) in Cycle I and further rose to 18 students (90%) in Cycle II, with the class average score reaching 82.5. These results indicate that the success indicators were achieved. The study concludes that the Problem Solving model is effective in increasing student engagement and learning outcomes, and it is suitable for implementation as an alternative instructional strategy at the elementary school level.